"Making Do" Decisions: How Home Healthcare Personnel Manage Their Exposure to Home Hazards. (April 2016) - Wills, Celia E.; Polivka, Barbara J.; Darragh, Amy; Lavender, Steven; Sommerich, Carolyn; Stredney, Donald
This study describes the decision-making processes home healthcare personnel (HHP) use to manage their personal health and safety when managing hazards in client homes. A professionally diverse national sample of 68 HHP participated in individual semi-structured interviews and focus group discussions, and described their decision making and strategies for hazard management in their work environments. HHP described 353 hazard management dilemmas within 394 specifically identified hazards, which were clustered within three broader categories: electrical/fire, slip/trip/lift, and environmental exposures. HHP described multiple types of "making do" decisions for hazard management solutions in which perceived and actual resource limitations constrained response options. A majority of hazard management decisions in the broader hazards categories (72.5%, 68.5%, and 63.5%, respectively) were classifiable as less than optimal. These findings stress the need for more support of HHPs, including comprehensive training, to improve HHP decision making and hazard management strategies, especially in context of resource constraints.